2023
DOI: 10.1007/s10565-023-09791-z
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 exposure increases dry eye disease risks through corneal epithelial inflammation and mitochondrial dysfunctions

Abstract: Dry eye disease (DED) is the most common disease affecting vision and quality of life. PM2.5 was a potential risk of DED. Herein, we conducted animal exposure and cell-based studies to evaluate the pathogenic effect of PM2.5 exposure on the ocular surface and DED etiological mechanisms. C57 mice were exposed to filtered air and PM2.5 aerosol. We assessed health conditions and inflammation of the ocular surface by corneal fluorescein staining and immunohistochemistry. In parallel, cultured human corneal epithel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Consistent with previous reports [31], we demonstrated that ROS are involved in cytokine and chemokine production in this co-culture system. PM 2.5 can induce DNA damage in corneal epithelial cells, probably by promoting ROS formation [13].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports [31], we demonstrated that ROS are involved in cytokine and chemokine production in this co-culture system. PM 2.5 can induce DNA damage in corneal epithelial cells, probably by promoting ROS formation [13].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, many studies have linked PM exposure to increased visits for several ocular diseases [39][40][41]. Current studies have reported that PM2.5 induces oxidative stress, inflammation [42], apoptosis [43], and autophagy [44] in the cornea. However, the signaling pathways underlying PM10 induced corneal damage are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have reported that PM 2 . 5 induces oxidative stress, inflammation [42], apoptosis [43], and autophagy [44] in the cornea. However, the signaling pathways underlying PM 10 induced corneal damage are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…A cell-based and animal exposure study was recently conducted by Chinese researchers, which proved that PM 2.5 would induce DED-related inflammatory response on corneal epithelial cells [17]. This study also explored its etiological mechanism: mitochondria of corneal epithelial cells are dysfunctional after PM 2.5 exposure, then the expression of anti-inflammatory protein Nrf2 was partly inhibited and the inflammatory protein P65 was activated, which eventually triggered an inflammatory reaction [17]. Titanium dioxide (TiO 2 ) nanoparticles, a noncombustible and fine crystalline powder, identified as the PM, were widely used in many commercial products [18].…”
Section: Ded and Pmmentioning
confidence: 99%
“…Several studies showed that PM exposure upregulated the levels of inflammatory cytokines (IL-1 β , IL-6, IL-8), induced oxidative damage and apoptosis, and decreased cell activity 10 , 12 , 14 , 15 , 16 . A cell-based and animal exposure study was recently conducted by Chinese researchers, which proved that PM 2.5 would induce DED-related inflammatory response on corneal epithelial cells 17 . This study also explored its etiological mechanism: mitochondria of corneal epithelial cells are dysfunctional after PM 2.5 exposure, then the expression of anti-inflammatory protein Nrf2 was partly inhibited and the inflammatory protein P65 was activated, which eventually triggered an inflammatory reaction 17 .…”
Section: Dry Eye Disease and Air Pollutantsmentioning
confidence: 99%